Sepsis-mediated renal dysfunction: Pathophysiology, biomarkers and role of phytoconstituents in its management - Balkrishna, Acharya; Sinha, Sugandh; Kumar, Ashwani; Arya, Vedpriya; Gautam, Ajay Kumar; Valis, Martin; Kuca, Kamil; Kumar, Dinesh; Amarowicz, Ryszard (Biomedicine & pharmacotherapy, 2023)
Sepsis has evolved as an enormous health issue amongst critically ill patients. It is a major risk factor that results in multiple organ failure and shock. Acute kidney injury (AKI) is one of the most frequent complications underlying sepsis, which portends a heavy burden of mortality and morbidity. Thus, the present review is aimed to provide an insight into the recent progression in the molecular mechanisms targeting dysregulated immune response and cellular dysfunction involved in the development of sepsis-associated AKI, accentuating the phytoconstituents as eligible candidates for attenuating the onset and progression of sepsis-associated AKI. The pathogenesis of sepsis-mediated AKI entails a complicated mechanism and is likely to involve a distinct constellation of hemodynamic, inflammatory, and immune mechanisms. Novel biomarkers like neutrophil gelatinase-associated lipocalin, soluble triggering receptor expressed on myeloid cells 1, procalcitonin, alpha-1-microglobulin, and presepsin can help in a more sensitive diagnosis of sepsis-associated AKI. Many bioactive compounds like curcumin, resveratrol, baicalin, quercetin, and polydatin are reported to play an important role in the prevention and management of sepsis-associated AKI by decreasing serum creatinine, blood urea nitrogen, cystatin C, lipid peroxidation, oxidative stress, IL-1β, TNF-α, NF-κB, and increasing the activity of antioxidant enzymes and level of PPARγ. The plant bioactive compounds could be developed into a drug-developing candidate in managing sepsis-mediated acute kidney injury after detailed follow-up studies. Lastly, the gut-kidney axis may be a more promising therapeutic target against the onset of septic AKI, but a deeper understanding of the molecular pathways is still required.
Keywords: Lipopolysaccharide Receptors; proteiny akutní fáze; lidé; Lipocalins; Sepsis; Peptide Fragments; Acute-Phase Proteins; peptidové fragmenty; Humans; Biomarkers; lipopolysacharidové receptory; Acute Kidney Injury; biologické markery; sepse; lipokaliny; akutní poškození ledvin